PEMERINTAHAN SULTAN HASSANAL BOLKIAH DAN PERBANKAN ISLAM DI BRUNEI DARUSSALAM (1984-2015M) - Sari, Surti Nurpita; ., Herawati (THAQAFIYYAT: Jurnal Bahasa, Peradaban dan Informasi Islam, 2018)
Brunei Darussalam is one of the country in Southeast Asia that has a good stability in economic. Natural resources are managed effectively and supported by various government policies become the main factor in supporting the nations economic progress. By the nations foundation of the Malay Islamic Beraja Philosophy (Falsafah Melayu Islam Beraja or MIB, Sultan Hassanal Bolkiah issues various policies including economics policies. Therefore, it is not surprising if most of the policies in Brunei Darussalam are based on Islamic teachings. In the field of monetary for example, the Sultan establishes an Islamic bank named Tabung Amanah Islam Brunei (TAIB) to prevent the public from interest or usury (riba). Sultan also sets a high tax and even prohibits the circulation of various commodities forbidden in Islam, such as khamr (kinds of alcoholic drinks forbidden in Islam as like wine and liquor), and others